Pandangan Tokoh Muhammadiyah Jember Pada Bank Syariah - Hidayatullah, M.F. Hidayatullah (LAN TABUR : Jurnal Ekonomi Syariah, 2023)
ABSTRACT Islamic banks have been operating in Indonesia for more than two decades. It carries out the main characteristics of transactions in accordance with sharia and halal way. It is shown that the market share of sharia banking in 2019 has only reached approximately 5.94% of national banking. One of the important problems faced by Islamic banking is the public's perception of doubting the sharia of Islamic banks. Whereas the sharia way is one of the characteristics and advantages of Islamic banks. The Muhammadiyah organization had delivered an earlier response to the existence of Islamic banking. Facing the current slowgoing development of Islamic banking, the people are supposed to pay attention to the views of Muhammadiyah leaders in Jember on Islamic banking. The results of this qualitative research stated that Muhammadiyah Jember figures believe that sharia banks have implemented sharia by carrying out the DSN MUI fatwa, even though it is not complete and still needs to make some improvements so that it is more trusted by the public Keyword:, Muhammadiyah leaders, Islamic banking, public perception.